Lower limb muscle pre-motor time measures during a choice reaction task associate with knee abduction loads during dynamic single leg landings - McLean, S. G.; Borotikar, B.; Lucey, S. M. (Clinical Biomechanics, 2010)
Female neuromuscular control during dynamic landings is considered central to their increased ACL injury risk relative to males. There is limited insight, however, into the neuromuscular parameters governing this risk, which may hinder prevention success. This study targeted a new screenable and potentially trainable neuromuscular risk factor. Specifically, we examined whether lower limb muscle pre-motor times, being the time between stimulus presentation and initiation of the muscle EMG burst, elicited during a simple choice reaction task correlated with knee abduction loads during separate single leg landings.